2013
DOI: 10.1016/j.gie.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Optical biopsy of sessile serrated adenomas: do these lesions resemble hyperplastic polyps under narrow-band imaging?

Abstract: Community gastroenterologists observed a profile of NICE features among SSAs that was intermediate to the profiles observed for HPs and adenomas. These results require confirmation by NBI experts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Other studies have shown similar low rates of diminutive sessile serrated adenoma/polyp in the rectosigmoid 27. We classified all serrated polyps as non-neoplastic (NICE Type 1), as endoscopic pattern and features of sessile serrated adenoma/polyp are more akin to those of hyperplastic polyps 28 29. Current optical diagnosis strategies endorse the resection of all right-sided colon polyps, and thus, there should not be increased apprehension that a right-sided sessile serrated adenoma/polyp would remain in situ if it was erroneously diagnosed as a hyperplastic polyp.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown similar low rates of diminutive sessile serrated adenoma/polyp in the rectosigmoid 27. We classified all serrated polyps as non-neoplastic (NICE Type 1), as endoscopic pattern and features of sessile serrated adenoma/polyp are more akin to those of hyperplastic polyps 28 29. Current optical diagnosis strategies endorse the resection of all right-sided colon polyps, and thus, there should not be increased apprehension that a right-sided sessile serrated adenoma/polyp would remain in situ if it was erroneously diagnosed as a hyperplastic polyp.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, premalignant SSA/Ps were not differentiated and equally often diagnosed as neoplastic as well as non-neoplastic polyps 18. Subsequently several experts stated that the resect and discard theory could only be implemented when proper endoscopic differentiation of SSA/Ps is possible 37 38.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, validated classification systems to distinguish ADs, HPs and SSA/Ps using NBI do not currently exist 9 11 12. A recent study showed that with the use of the NBI International Colorectal Endoscopic (NICE) criteria, SSA/Ps are as often accounted as neoplastic as well as non-neoplastic polyps, which may limit the applicability of the NICE criteria in practice 18. In the past years, specific endoscopic features to characterise SSA/Ps have been described and could potentially be used to optimise the accuracy of optical diagnosis of colonic polyps, including SSA/Ps 19–22…”
Section: Introductionmentioning
confidence: 99%
“…The majority of sessile serrated adenomas might have been excluded from this study because they can share many features of hyperplastic polyps. 24,25 Delayed postpolypectomy bleeding could not be evaluated because additional EMR was performed to evaluate the presence of residual tissues after each polypectomy. The complete resection rates for adenomatous polyps %4 mm were not significantly different between the CSP group and the CFP group in our study.…”
Section: Discussionmentioning
confidence: 99%